Результаты лабораторных и натурных исследований береговых процессов водохранилищ Беларуси - Kobyak Валерий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
The results of plain reservoir’s banks abrasion process laboratory modeling for Belarus are presented. These processes are found in connection with changing of exploitation regime (e.g. reconstruction, conservation zone increment, change of operations schedule, etc.). Reconnaissance and stationary field observation traced at testing water objects from 2004 till 2010 allowed to analyze marginal erosion intensity and scale.